Water Quality Assessment for Mariculture in the Waters of Legundi Island, Pesawaran District, Indonesia - Adrian Restuputra Sasongko; Nasuki; Kartika Primasari; Suryanti; I Gusti Ngurah Permana (Advances in Tropical Biodiversity and Environmental Sciences, 2025)
Indonesia has an extensive maritime zone, but its fisheries production achievement remains low. The potential of this marine area should be optimally utilized to boost mariculture production. This study aims to analyze the suitability level of the waters around Legundi Island for use as a mariculture site. The research method used is descriptive statistical analysis. Data collection was conducted at 12 sample points, determined using the purposive sampling method, through on-site observations and the interpretation of Google satellite images. Sample points were distributed at each location near residential areas. The results of this study show that the waters of Labuan Agung have the highest value, with an average of 96.5%, while the waters of Selesung have the lowest value at 91.6%. Overall, the waters around Legundi Island fall into the S1 (very suitable) classification with an average score of 93.8%. In conclusion, Legundi Island possesses regional characteristics that indicate significant potential for mariculture development.